Comparative Study on Green Monopropellants for Rocket Engines - Janani Kavipriya VS; Bhushan Chavan, Krithika C, Boparai Manmeetkaur Ajmersingh (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2022)
The current trend in rocket propulsion is to make propellant consumption more environmentally friendly. Green propellants have a higher economic value due to their beneficial qualities, which allow them to save money on transportation, storage, and handling while also reducing ground operations time. The cost of transporting and handling hydrazine puts a strain on the space industry. So, the greening of classical hydrazinebased propulsion systems is recommended by many space agencies.Many spacecrafts currently use green propellants for space missions, which have environmental and safety concerns in small satellites and nano satellites that operate in planetary orbits. In this article, a selected number of promising green space propellants are reviewed by their performance parameters along with the physical and chemical properties.